Balancing Control and Trust to Manage CSR Compliance in Supply Chains - Akmal S. Hyder; Ehsanul Huda Chowdhury; Agneta SundstrÃ¶m (International Journal of Supply Chain Management, 2017)
This study examines how buyers and suppliers balance control and trust to manage compliance with corporate social responsibility (CSR) requirements in supply chains (SCs). Two indepth qualitative case studies of the Bangladesh apparel industry on two multinational companies of the same european country were conducted. This study indicates that a buyer's need for control and trust is important in contact with other actors for managing CSR compliance in supply chains. This study analyzes control and trust to fill an important gap in Sc theory on relationships by stressing how these constructs, interact and complement each other to manage CSR compliance in apparel industry. This study notes that managers need bothe formal and informal control to create competence and intentional trust in the supplychains